Impulsive Caputo-Fabrizio fractional differential equations in b-metric spaces - Lazreg Jamal Eddine (De Gruyter, 2021)
We deal with some impulsive Caputo-Fabrizio fractional differential equations in bb-metric spaces. We make use of α-ϕα \text{-}φ -Geraghty-type contraction. An illustrative example is the subject of the last section.